Enhancement of mechanical and rheological properties of PA-12 through silane modification - Jadhav, V. Pravin; Mahajan, Digvijay; Patil, Prashant; Umbarkar, Shubhangi B.; Pol, Harshawardhan (Bulletin of Materials Science, 2025)
This research examines the effects of silane modifications on polyamide 12 (PA-12) to improve its mechanical and thermal properties. The study employs a reactive extrusion technique to integrate various silanes-Dynasylan (R) AMEO, Dynasylan (R) 1189, Dynasylan (R) DAMO and Dynasylan (R) VPS 4721-at different concentrations (0.25, 0.5 and 0.75%). Key findings reveal that silane modifications significantly enhance the tensile strength, impact resistance and viscoelastic behaviour of PA-12, with the Dynasylan (R) DAMO formulation achieving the highest tensile strength of 38.25 MPa vis-& agrave;-vis 8.02 MPa for PA-12. The modifications also resulted in a reduction of crystallinity by over 35%, contributing to improved toughness and impact strength. Rheological assessments indicate that the flow properties of PA-12 are positively altered, enhancing its complex viscosity and storage modulus, which are crucial for applications in automotive and aerospace industries. Thermal analysis through differential scanning calorimetry and thermogravimetric analysis confirms improved thermal stability, particularly in the 0.5% Dynasylan (R) AMEO-modified sample, exhibiting an onset temperature of 421.87 degrees C. The study emphasizes the importance of the silane type and dosage in tailoring PA-12's performance for advanced applications, suggesting future research directions to further refine silane-modification techniques for enhanced polymer performance. This research provides valuable insights into polymer-modification strategies, highlighting the potential for silane treatments to optimize the mechanical, thermal and rheological properties of PA-12 for diverse industrial applications.
Keywords: mechanical properties; Polyamide 12 (PA-12); reactive extrusion; rheological behaviour; silane modification; thermal stability